An intentionally unfair trial - Doebbler, Curtis F. J. (Journal of international criminal justice, 2010)
Numerous flaws made the Dujail trial a violation of the internationally protected human right to a fair trial. The United States and the Iraqi authorities conducted an unfair trial knowing that both the Third and Fourth Geneva Convention describe wilfully depriving a person of the rights of fair and regular trial as a war crime. Even if Saddam Hussein was not to be regarded as a prisoner of war, that is, merely as a civilian, in any case his right to fair trial was protected by international law. According to the author, both the relevant states and the individuals involved in the unfair Dujail trial bear responsibility for breaches of international law